A Physical Activity Learning Module Improves Medical Students' Skills and Confidence for Advising Patients about Physical Activity - Sandra Mandic; Hamish Wilson; Monika Clark-Grill; Diana O'Neill (Montenegrin Sports Academy, 2018)
Physicians' knowledge, confidence, and prior training will influence physical activity (PA) counselling in general practice. This study evaluated the effects of a PA learning module on knowledge, skills, and attitudes toward PA counselling in third-year medical students. Students (n=216; age: 21.1±2.2 years; 47% males; participation rate 91%) participated in a PA learning module that included tutorials, lectures, and experiential learning through providing health checks to adults. At baseline and four months after the intervention, students completed a paper questionnaire about their awareness of current PA guidelines, benefits of, and attitudes toward PA advising, perceived competence/importance of PA advising skills, and personal PA habits. Data were analysed using a t-test for dependent samples and Chi-square analysis. After the intervention, students reported a greater awareness of the PA guidelines (pre vs. post: 3.1±1.1 vs. 3.8±0.9), the national PA initiative (4.2±0.9 vs. 4.7±0.7), the importance of PA counselling in general practice (4.1±0.8 vs. 4.3±0.8), and their confidence (3.2±0.9 vs. 3.9±0.8), and perceived competence (3.1±0.8 vs. 3.8±0.8, all p<0.05) in providing PA advice compared to baseline. In conclusion, exposure to a PA learning module increased medical students' awareness and knowledge of the current PA guidelines and improved their confidence and perceived competence in providing PA advice. However, even after the training, students on average perceived themselves to be only moderately competent in providing PA advice. Therefore, clinical training for medical students should be designed to improve students' competence and skills in PA counselling